1977
DOI: 10.1073/pnas.74.9.3720
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA from oncornavirus-infected cells enriched in virus-specific DNA sequences

Abstract: We previously found that a minor fraction of single-stranded DNA (ss-DNA) isolated from native nuclear DNA of normal chicken embryonic cells and cells of other species hybridized with bulk nuclear DNA or cellular RNA in great excess. At least one-third of ss-DNA belonging to the nonrepetitious part of the cell genome could be hybridized to homologous RNAs. In the present work, similar results were obtained with ss-DNA from cells of chickens infected by avian myeloblastosis virus (AMV). To investigate whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…consisting of single-stranded molecules, is related to synthesis of numerous RNA species [4--61. It was demonstrated that the ssDNA from chicken leukemic cells productively infected by avian myeloblastosis virus [5] or ssDNA from mouse cells non-productively transformed by simian virus (SV40) (Shaool, D. et al. unpublished results) are greatly enriched for DNA sequences encoding the viral RNA, but contain no or very few sequences from the non-transcribed DNA strand.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…consisting of single-stranded molecules, is related to synthesis of numerous RNA species [4--61. It was demonstrated that the ssDNA from chicken leukemic cells productively infected by avian myeloblastosis virus [5] or ssDNA from mouse cells non-productively transformed by simian virus (SV40) (Shaool, D. et al. unpublished results) are greatly enriched for DNA sequences encoding the viral RNA, but contain no or very few sequences from the non-transcribed DNA strand.…”
Section: Discussionmentioning
confidence: 99%
“…The amounts hybridized were determined by treating aliquots with S1 nuclease and measuring the acid precipitates collected on GF/B nitrocellulose Wathman filters, in a scintillation spectrometer as previously indicated [5] for 'H or in a Gamma 4000 Beckman counter at 70% efficiently for '"I.…”
Section: Nucleic Acid Hybridizationmentioning
confidence: 99%
See 3 more Smart Citations